The dominant borrower syndrome. Issue 49 (20th October 2016) - Choudhary, M. Ali; Khan, Sajawal; Pasha, Farooq; Rehman, Muhammad
ABSTRACT: The financing channel of a fiscal stimulus matters for the size and the sign of the fiscal multiplier. We develop a general equilibrium model where a fiscal stimulus is partially bank-funded and the government becomes the dominant borrower from banks relative to entrepreneurs. This leads to a negative impact on credit spreads, investment and a contraction in output. We support our story with a structural vector autoregression for a sample of developing countries featuring the dominant borrower syndrome.